2020
DOI: 10.14202/vetworld.2020.579-585
|View full text |Cite
|
Sign up to set email alerts
|

Babesia canis spp. in dogs in Baghdad Province, Iraq: First molecular identification and clinical and epidemiological study

Abstract: Aim: The aim of this study was to investigate babesiosis in dogs of different breeds and ages and of both sexes in Baghdad Province by molecular detection of Babesia canis using conventional polymerase chain reaction (PCR) and sequencing followed by phylogenetic analyses. Materials and Methods: Blood samples were collected from 310 dogs of different ages and breeds, and of both sexes in different areas of Baghdad Province from December 2018 to September 2019; during clinical examinations, body tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In this study, B. vogeli was detected in 18 (5.34%) of 337 blood samples. The prevalence of the parasite was 2.1% in Malaysia [ 37 ], 4.8% in Brazil [ 38 ], 5.1% in Egypt [ 39 ], 5.1% in Iraq [ 40 ], 8.5% in Bosnia and Herzegovina [ 41 ], 9.3% in Iran [ 42 ], and 10.8% in Nigeria [ 43 ]. When the studies given above were evaluated, it was seen that the prevalence of B. vogeli was quite different.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, B. vogeli was detected in 18 (5.34%) of 337 blood samples. The prevalence of the parasite was 2.1% in Malaysia [ 37 ], 4.8% in Brazil [ 38 ], 5.1% in Egypt [ 39 ], 5.1% in Iraq [ 40 ], 8.5% in Bosnia and Herzegovina [ 41 ], 9.3% in Iran [ 42 ], and 10.8% in Nigeria [ 43 ]. When the studies given above were evaluated, it was seen that the prevalence of B. vogeli was quite different.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, hematological changes are described in wandering canines with blood diseases of parasitic origin. According to Badawi and Yousif (2020), street animals or animals with free access to this environment are more predisposed to acquire hemoparasites. Studies conducted in Brazil have shown the occurrence of hemoparasitoses with infections between Anaplasma platys, Erhlichia canis, Babesia canis, Hepatozoon canis and Leishmania infantum (SANTOS et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of this study as mentioned in a recent study by Badawi and Yousif [ 12 ] provides the molecular record and phylogenetic analysis of B. canis in dogs in Iraq, and it will be valuable to confirm clinical signs and study epidemiological risk factors of babesiosis in dogs. However, various species from the genus Babesia ( B. canis , Babesia vogeli , and Babesia rossi ) cannot be differentiated through microscopic examination of blood films, despite differences in their genetics, pathology, and vector associations [ 13 ].…”
Section: Introductionmentioning
confidence: 98%